Altered states, alkaloids, and catatonia: Monoaminoxidase inhibitors and their role in the history of psychopharmacology - Buda, Octavian; Hostiuc, Sorin; Popa-Velea, Ovidiu; Boroghina, Steluta (Frontiers in Pharmacology, 2022)
Monoamine oxidases are mitochondrial enzymes that catalyze the oxidative deamination of biogenic amines (adrenaline, noradrenaline, serotonin, and dopamine), causing their inactivation and subsequently playing a fundamental role in the homeostasis of various neurotransmitters. As the regulation of these effects was deemed important in clinical practice, numerous modulators of these enzymes were tested for various clinical effects. The purpose of this paper is to present a few historical landmarks regarding monoaminoxidase inhibitors and their usefulness as psychopharmacological agents. We will be focusing on banisterine, iproniazid, selegiline, rasagiline, tranylcypromine, moclobemide, and their role in the history of psychopharmacology. An almost unknown fact is that harmine, an MAO-A alkaloid, was used as early as the latter half of the 1920s in Bucharest, to reduce catatonic symptoms in schizophrenia, thus ushering the dawn of psychopharmacology era which started with chlorpromazine in the 1950s.